Analysis of the indoor thermal environment of traditional residents in the South Sichuan China region in summer and plum rainy seasons—taking Baiyang village in Yibin city as an example - Yan Zhang; Luting Xu; Biao Wang (Journal of Asian Architecture and Building Engineering)
In hot summer and cold winter areas, the humid and sultry summer and rainy season problems have long affected the health of residents. Through a questionnaire survey and site measurements, the indoor thermal environment of typical southern Sichuan village houses was investigated. The average indoor humidity of the old traditional dwelling (85–95%) in the rainy season was much greater than that of the new rural house (70–80%), both of which are outside the standard thermal comfort range of the human body. In summer, the situation is slightly better but still uncomfortable. The APMV evaluation results reveal that in the rainy season, the new residential house is more comfortable than the traditional residential house, while in summer, the opposite situation occurs. The measurements show that the thermal inertia index of the old stone masonry house is large, which indicates that the house has a strong ability to resist temperature fluctuations. Therefore, we discussed different performance improvement strategies for these two types of rural residences. This study is conducive to improving the thermal environment of local residential buildings and provides a reference for the future design of rural ecological residential buildings.